Geology of the Palladium-rich Legris Lake Mafic-Ultramafic Complex, Western Wabigoon Subprovince, Northwestern Ontario - Neil T. Pettigrew; Kéiko H. Hattori (Canadian Institute of Mining, Metallurgy and Petroleum, 2001)
"Abstract- The Legris Lake Complex is a northeast-trending, 7.3 km long by 3.5 km wide, maficultramafic intrusive complex located in the western Wabigoon Subprovince of the Archean Superior Province. It is one of a series of mafic-ultramafic igneous complexes, the most notable of which is the Lac des Iles Complex, host to Canada’s only producing Pd mine with reserves of 93.5 Mt grading 1.53 g/t Pd as of December 2001 (North American Palladium Ltd., Annual Report 2001). Cu-Ni- PGE mineralization was first discovered in the Legris Lake Complex by a local prospector late in 1999. Shortly thereafter, the property was jointly optioned by Avalon Ventures Ltd. and Starcore Resources Ltd., who continue to discover significant Cu-Ni-PGE mineralization.One of the most notable features of the Legris Lake Complex is the occurrence of extensive brecciation caused by multiple injections of volatile-rich magma. The Cu-Ni-PGE mineralization is hosted by leucogabbro within a 2 km long by 600 m wide, highly brecciated area in the northwestern area of the Complex. The mineralized rocks contain disseminated to blebby sulfides (1 to 5 vol.%), comprising chalcopyrite + pyrite ± pyrrhotite + millerite ± pentlandite, typically surrounded by epidote. The majority of the Cu-Ni-PGE mineralization displays low ratios of Pt/Pd (~0.20) and high ratios of Cu/Ni (~2.9), which are similar to those of the Lac des Iles and the River Valley mafic-ultramafic complexes. The lithologies in Legris Lake Complex bear similarities to the heterolithic gabbro of the Twilight and Roby Zone deposits at the nearby Lac des Iles mine. However, the mineralization at Legris Lake, which is restricted to leucogabbro overlying unmineralized clinopyroxenite, is similar to that of stratiform deposits such as the Stillwater and Munni Munni complexes. The mineralization at Legris Lake is best explained by the late-stage, immiscible separation of a sulfide melt from volatile-rich parental magmas and the subsequent minor redistribution of metals by deuteric fluids."